Lessons from medicolegal cases in obstetrics and gynaecology : improving clinical practice / edited by Swati Jha, Eloise Power. - Jha, Swati; Power, Eloise (Cambridge medicine (Series), 2022)
Obstetrics and gynaecology is the biggest area of medical litigation, with compensation pay-outs exceeding the rest of medicine combined. Many specialists working in the field will be sued over their professional lifetime - having an increased awareness of past cases and their implications will reduce the risk of future litigation. Using landmark cases in the field, this book covers scenarios such as multiple pregnancy, hysterectomy and breech delivery, describing factors that have led to litigation. Chapters are structured clearly, beginning with case commentaries detailing both a successful and unsuccessful claim. This section is followed by legal commentary explaining the relevant laws and the verdict, finally giving a clinical commentary provided by experts in the field which focuses on best practice to avoid litigation. Edited by an accredited expert witness in the field and a barrister specialising in medical law, this is an invaluable resource for clinicians and lawyers alike.